Using handhelds to support students' outdoor educational activities. (17th February 2010) - Churchill, Daniel; Kennedy, David; Flint, David; Cotton, Nick
This paper discusses a pilot study involving the use of handheld computers (portable digital assistants, PDAs) with a group of secondary school students engaged in a fieldtrip. Throughout the six-day trip to Northern Thailand, students engaged in variety of educational activities, with the aim of acquiring some of the key concepts and skills that are part of the Year 12 geography curriculum. To support their learning each student was provided with a PDA. Throughout the study, student use of handhelds for data collection, collaboration and reflection was observed. In addition, qualitative data from participant observations and interviews were gathered. Analysis of the data has resulted in the development of a better understanding of the potential educational applications for handhelds used during outdoor educational activities. Analysis of the data has resulted in a number of recommendations for optimal use of PDAs in fieldwork. The potential benefits for learning are discussed.